THE QUALITY OF IT PROJECT MANAGEMENT: THE BUSINESS PROCESS AND THE APPLICATIONS GO PROJECT LEAN - Nusraningrum, Dewi (Manajemen Bisnis, 2020)
This study analyzed dominant aspects that affect the quality of software-based project development from the point of view of project management. The purpose of this study is to determine the effect of Business Process and Application Go Project Lean (GPL) on the Quality of Information Technology Project Management. The research method used is a survey. The population is users of Go Project Lean Application Division Sales Division, Project Management Office Division, and Aplication Development Division. Instrument Analysis used Validity and Reliability Test, F Test (Simultaneous Test), Fit Model Test. The Hypothesis Testing using t test (Partial Test), and Multiple Linear Regression Test, and Inter-Dimensional Correlation Test. The results showed that the Influence of Business Process and GPL Application is very Strong and Significant to the Quality of IT Project Management. There is no Investment feasibility analysis calculation application that affects on time delivery.